FISHERMEN’S PERCEPTION ON PORTABLE COOLING MACHINES WITH SOLAR PANELS AT BATU BERIGA, CENTRAL BANGKA REGENCY - Imron, Mohammad; Wisudo, Sugeng Hari; Baskoro, Mulyono S.; Uju; Triadhi, Joko; Soehadi, Imam; Kurnia, Triono Aries; Arzali; Anggraini, Atika; Kusumastuti, Ratih; Wardani, Puti; Prasetiyo, Shidiq Lanang (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
This study aims to analyze the perceptions of Batu Beriga fishermen regarding the use of portable cooling machines powered by solar panels as an alternative to ice in handling fish catches. The technology is considered promising as it reduces dependence on ice blocks, lowers operational costs, and helps maintain fish freshness for longer periods. A descriptive quantitative approach was employed, using a structured questionnaire administered to 40 active fishermen with at least five years of fishing experience. Perceptions were assessed through 10 indicators covering functionality, economic benefits, ease of use, compatibility, technical complexity, and impact on catch quality. The results reveal that most fishermen expressed positive perceptions, with the highest agreement on the machine’s function as an ice substitute (95%) and its adaptability to vessel conditions (90%). However, concerns remain regarding the initial investment cost and fabrication complexity, as only 50% of respondents agreed with this aspect. Overall, the findings highlight a strong relative advantage and compatibility, while technical complexity persists as a major challenge. The study underscores the need for policy support in the form of technology subsidies, soft loans, and technical training programs to facilitate wider adoption. Such interventions are expected to accelerate the integration of renewable energy technologies into small-scale fisheries, reduce fishermen’s operational costs, and strengthen post-harvest handling systems. Furthermore, the adoption of solar-powered cooling technology aligns with the Sustainable Development Goals (SDGs), particularly Goal 7 (Affordable and Clean Energy) and Goal 14 (marine ecosystem). Key words: Bangka Tengah, fishermen, perception, portable cooling machine, solar panel